The level of serum C-peptide signals fibrosis in obese patients with NAFLD - May Mohsen Fawzi; Ghada Rabea Abd El Aziz; Reham Alaa El Din Mohamed; Manal Mohamed Kamal; Ahmed El Shenawy (The Egyptian Journal of Internal Medicine)
Abstract Nonalcoholic fatty liver disease (NAFLD) is considered one of the most common causes of chronic liver disease worldwide. Various scoring systems have been developed using different biomarkers to aid in the identification of fibrosis associated with NAFLD. The role of C-peptide in the pathophysiology of liver fibrosis has become an increasingly important topic of research. Objective To correlate C-peptide level with NAFLD assessed by NFS and ultrasonography. Methods This study involved 118 participants, who were categorized into four groups based on ultrasound findings and BMI: the obese non-NAFLD group, the obese NAFLD group, the non-obese non-NAFLD group, and the non-obese NAFLD group. Anthropometric data (height, weight, BMI, and waist circumference), CBC, fasting blood glucose, 2-h postprandial blood glucose, HbA1c, ALT, AST, serum albumin, lipid profile, C-peptide, NFS, and abdominal ultrasound were done for all participants. Results Serum C-peptide levels demonstrated a statistically significant difference between the studied groups. C-peptide showed a strong positive correlation with weight, TG, with a p-value of 0.0001. The NFS was positively correlated with C-peptide. Abdominal US proved to be more effective than NAFLD scores in detecting fibrosis, with sensitivity rates of 100% compared to 44.1%. Conclusion There is a notable link between serum C-peptide levels and NFS found. C-peptide was strongly positively correlated with weight and dyslipidemia. NAFLD fibrosis score was moderately positively correlated with C-peptide. Abdominal ultrasonography was superior to NAFLD scores in the detection of fibrosis.